The Role of Green Innovations and Mechanisms of Their Implementation in Small Business and Private Entrepreneurship (KIUT Publication, 2025)
This article scientifically and practically explores the importance of green innovations in the activities of small businesses and private entrepreneurship, as well as the mechanisms for their implementation. The study provides an in-depth analysis of the concept of green innovations, their impact on economic and environmental efficiency, and their role in enhancing the competitiveness of small business entities. Based on international experience, the author develops key mechanisms for integrating green innovations into entrepreneurial activities and offers practical recommendations. In addition, the article thoroughly discusses the main challenges that arise during the implementation of green innovations and the possible solutions to address them.